Validation of the Persian Cultural Intelligence Scale and Exploring its relationship with Gender, Education, Travelling abroad and Place of Living (Global Journal of Human-Social Science, 2011)
This study explored the validity of Cultural Intelligence Scale CQS and its relationship with gender education travelling abroad and place of living in Iran The Persian version of CQS was administered to 854 undergraduate and graduate students majoring in five broad branches of knowledge in three different state universities in Iran When the Principal Axis Factoring was employed and the latent variables were rotated via Varimax with Kaiser Normalization four factors were extracted whose number was the same as other studies but differed in their order i e Cognitive Motivational Behavioral and Meta-cognitive While the students coming from underprivileged cities had significantly higher total cultural intelligence CQ as well as Cognitive Motivational Behavioral and Meta-cognitive CQs female participants Meta-cognitive CQ was higher than the male Whereas graduate participants showed significantly higher Cognitive and Behavioral CQs the participants who had not traveled abroad surpassed their travelling counterparts not only in total CQ but also in Cognitive Motivational Behavioral and Meta- cognitive CQs These findings suggest the role of cultural intelligence in learning and developing mega skills such as understanding cultural identity and checking cultural lenses and emphasize its state-like nature
Keywords: Factor analysis; cultural intelligence; gender; education; place of living